Stepping towards sustainability: exploring the feasibility and impact of recycling plastic footwear - Sakib, Fazle Rabbi (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.